Assignment of spectrum demands by merits via analytic hierarchy process and integer programming - Ramli, Razamin; Jamaluddin, Faathirah; Engku Abu Bakar, Engku Muhammad Nazri; Alias, Mohamad Yusoff; Mahat, Nor Idayu; Abdul Karim, Mohd Zaini (Universiti Utara Malaysia Press, 2013)
Demand for wireless services is ever increasing due to wireless technology advances, which directly relates to the increasing demand for spectrum bandwidths. Due to the high demand, thus spectrum has become scarce.As a result, spectrum bandwidths have become important and need to be efficiently assigned to potential and demanding service providers.Thus, this paper proposes an integrated approach to solve a spectrum assignment problem.The integrated model is developed to efficiently determine the optimal spectrum assignment for the purpose of satisfying the identified relevant requirements and constraints or criteria.The development of the model has also taken into consideration the situation when the spectrum regulator wishes to choose the best provider or licensee based on merits.For that purpose, suitable weights based on qualitative criteria were obtained via Analytic Hierarchy Process and subsequently used as coefficients in the respective Integer Programming formulation. The integrated optimization model is able to tackle a multi-criteria spectrum problem and then solve the assignment problem by way of maximizing the total efficiency. The results exhibits a more efficient alternative as compared to the existing qualitative approach, as it is able to combine subjective judgments computation with a mathematically formulated approach to produce a systematic and consistent results.